2009
DOI: 10.1002/ijc.24459
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulates human vitamin D receptor

Abstract: Most of the biological effects of 1a, 25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) are elicited by the binding to vitamin D receptor (VDR), which regulates gene expression. Earlier studies reported no correlation between the VDR protein and mRNA levels, suggesting the involvement of posttranscriptional regulation. MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression through translational repression or mRNA degradation. A potential miR-125b recognition element (MRE125b) was identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
3
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 34 publications
7
135
3
4
Order By: Relevance
“…Two recent studies reported that miR-125b may act as an oncogene in human breast cancer cells. One study reported that miR-125b promoted cell proliferation and decreased the antitumor effects of 1,25(OH)(2)D(3) in breast cancer MCF7 cells (52). Another study showed that compared with nontumorigenic cancer cells, miR-125b is overexpressed in highly tumorigenic human breast cancer stem cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that miR-125b may act as an oncogene in human breast cancer cells. One study reported that miR-125b promoted cell proliferation and decreased the antitumor effects of 1,25(OH)(2)D(3) in breast cancer MCF7 cells (52). Another study showed that compared with nontumorigenic cancer cells, miR-125b is overexpressed in highly tumorigenic human breast cancer stem cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been reported that miR-27b (MIR27B) and miR-298 (MIR298) reduce VDR levels in LS-180 colon cancer cells (Pan et al 2009). In addition, Mohri et al (2009) have shown that miR-125b (MIR125B) down-regulates VDR expression and reduces 1,25(OH) 2 D 3 action in breast cancer cells. Interestingly, miR-125b has been found to be over-expressed in colon cancer metastases (Baffa et al 2009).…”
Section: Angiogenesismentioning
confidence: 99%
“…However, the miRNA:mRNA pairs largely remain to be identified. Recently, we reported that miRNAs were involved in the regulation of human xenobiotics-metabolizing enzymes such as CYP1B1 (Tsuchiya et al, 2006) and CYP2E1 (Mohri et al, 2010) and human nuclear receptors such as pregnane X receptor (Takagi et al, 2008), vitamin D receptor (Mohri et al, 2009), and hepatocyte nuclear factor 4α (Takagi et al, 2010). As a sequel study, we focused on human aryl hydrocarbon receptor nuclear translocator (ARNT).…”
Section: Introductionmentioning
confidence: 99%